The World at Arms: Reader's Digest Illustrated History of World War II - Editor Wright, Michael [et al.] (London Reader's Digest Asso., 1989)
The definitive one volume source on World War II includes more than 3,000 photographs, maps, drawings, and re-enactments--many in full color. Covers all fronts, all sides, minor actions as well as major events, great commanders, ordinary fighting men and more.
Includes Colored Illustrations and Index
Keywords: World War, 1939-1945